Sensitization to Mites and Total IgE in Allergic Children - Nivia López Ramírez; Marisela L. Pérez Pacaréu; Vivian Macías Carrera; Andrés Osquel Benítez Goitizolo; Innery Rosell García; Isabel Vega Bolaño (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Incidence and prevalence of allergic diseases during childhood have significantly increased in developed countries over the last 20 to 30 years. The role of the inhalant allergens in exacerbating respiratory allergies has been demonstrated. House dust mites are the main causative agents. Environmental pollution and climate changes, along with other factors, have contributed to the increase of these diseases. Among such conditions the most frequent in children are respiratory allergies, particularly allergic rhinitis and bronchial asthma. The current article presents a review on allergic rhinitis, bronchial asthma and IgE levels in children, emphasizing on epidemiology and trigger factors.